Attenuation of the physiological response to infection on adults over 65 years old admitted to the emergency room (ER) (2017)
ABSTRACT: It has been considered that the elderly have clinical manifestations different from the ones observed in middle-age adults during an injury event. This hypothesis has not been extensively explored in sepsis and bacterial infections. Secondary analysis of two prospective studies including 2611 patients over 18 years of age admitted to the emergency room with confirmed or probable bacterial infections and sepsis. The outcome measures were heart rate, respiratory rate, systolic blood pressure, temperature, Glasgow Coma Scale, creatinine, PaO2/FiO2 and platelets daily during the first week. Compared to survivors younger than 65, the deceased under 65 had an average heart rate of 12.5 beats per minute per day higher (95% CI 9.32; 15.61), while patients over 65 who died barely had an average 5.7 beats per minute per day higher than the same reference group (95% CI 3.45; 8.06). The systolic blood pressure had a significant decreased in those who died younger than 65, compared to survivors with the same age, in both cohorts